Evaluation of the In-Vitro Effects of Albendazole, Mebendazole, and Praziquantel Nanocapsules against Protoscolices of Hydatid Cyst - Nooshinmehr Soleymani; Soheil Sadr; Cinzia Santucciu; Abbas Rahdar; Giovanna Masala; Hassan Borji (Pathogens, 2024)
Cystic echinococcosis still remains a serious health and economic problem worldwide. The etiologic agent is Echinococcus granulosus sensu lato, giving origin to a fluid-filled cystic lesion. Therapy faces several challenges. Nanodrugs have shown promise as chemotherapeutics against hydatid cysts. The present study evaluated a highly safe lipid nano-polymeric capsule for its superior efficacy and ability to overcome drug resistance. Nanocapsule drugs were formulated into six groups: Albendazole, mebendazole, praziquantel, albendazole + mebendazole, albendazole + praziquantel, and praziquantel + mebendazole. The protoscolicidal effects of these six groups were assessed at 10, 60, and 120 min in three concentrations (1, 0.5, and 0.25 mg/mL). Drug formulations were evaluated via zeta potential, droplet size, solubility, particle size analyzer (PSA), and scanning electron microscopy. According to the PSA results, the mean size of the albendazole nanocapsules was 193.01 nm, mebendazole was 170.40 nm, and praziquantel was 180.44 nm. Albendazole + mebendazole showed the greatest protoscolicidal activity at a concentration of 1 mg/mL after 120 min. In contrast, each drug’s 0.25 mg/mL single-dose times showed the least protoscolicidal activity after 120 min. With the right application of nanotechnology, it is possible to produce safe and effective drugs, such as the polymeric combination of albendazole and mebendazole, which has promising implications.